Nitrogen-Sulfur And Nitrogen-Boron Co-Doped Biochar As Peroxymonosulfate Activator For Fluoroquinolone Antibiotics Removal - Choong, Zheng Yi (2023)
Recently, the application of multi-heteroatom-doped carbocatalyst in peroxymonosulfate (PMS)-based advanced oxidation processes for removing recalcitrant pollutant has been increasingly studied. As the studies on multi-heteroatom-doped carbocatalyst in PMS activation is still nascent, the main objective of this study is to study various multi-heteroatom-doped biochar for PMS activation. In the first part of the study (Chapter 4), a series of N, S-co-doped biochar (BSN-Ts) were prepared at different temperature using one-step calcination method. Through various characterization, it was found that g-C3N4 was first formed by polymerization of urea and thiourea, and engulf the biochar. At higher synthesis temperature, the g-C3N4 decomposed and coalesce with the biochar, forming BSN-Ts. The performance of BSN-Ts as PMS activators for gatifloxacin (GAT) removal were evaluated and were found that BSN-Ts prepared at 800 oC (BSN-800) showed the greatest performance due to its relatively high specific surface area (SBET = 419 m2 g-1) and synergism between heteroatoms.